Ex Vivo Biomechanical Assessment of a Novel Multi-Strand Repair of Canine Tendon Lacerations - Curcillo, Chiara P.; Duffy, Daniel J.; Chang, Yi-Jen; Moore, George E. (Veterinary and Comparative Orthopaedics and Traumatology, 2021)
Objective This study aimed to evaluate the effect of increasing the number of suture strands traversing the transection site, level of suture purchase and depth of suture penetrance on the biomechanical properties of repaired gastrocnemius tendons.Study Design Thirty-eight adult cadaveric gastrocnemius tendons were randomized, transected and repaired with either two-, four- or six-strand locking multi-level repair. Tensile loads required to create a 1 and 3 mm gap, yield, peak and failure loads and failure mode were analysed. Significance was set at p < 0.05.Results Mean ± standard deviation yield, peak and failure force for six-strand repairs was 90.6 ± 22.1 N, 111.4 ± 15.2 N and 110.3 ± 15.1 N respectively. This was significantly greater compared with both four-strand (55.0 ± 8.9 N, 72.9 ± 7.8 N and 72.1 ± 8.2 N) and two-strand repairs (24.7 ± 8.3 N, 36.5 ± 6.0 N and 36.1 ± 6.3 N) respectively (p < 0.001). Occurrence of 3 mm gap formation was significantly less using six-strand repairs (p < 0.001). Mode of failure did not differ between groups with all repairs (36/36; 100%) failing by suture pull-through.Conclusion Pattern modification by increasing the number of suture strands crossing the repair site, increasing points of suture purchase from the transection site and depth of suture penetrance is positively correlated with repair site strength while significantly reducing the occurrence of gap formation in a canine cadaveric model. Additional studies in vivo are recommended to evaluate their effect on tendinous healing, blood supply and glide resistance prior to clinical implementation.
Keywords: biomechanical properties; tendon repair; suture; canine tendon injury; animal models of human disease